Health prevention in the pediatric population - challenges and recommendations for the future - Antos-Łyko, Maria; Wasąg, Oliwia Regina; Koszuta, Karina Aleksandra; Koszuta, Przemysław; Tkaczyk, Marcin; Pająk, Dawid; Czerniak, Piotr; Buszek, Julia; Laskowska, Paulina; Pistelok, Adrian (Journal of Education, Health and Sport, 2025)
Introduction and purpose: The aim of this work is to deepen the topic of health prevention and to draw attention to the need for early intervention, a holistic approach to health and cooperation between family, school and health care. Popularization of knowledge about a healthy lifestyle, including breastfeeding, physical activity and prevention of lifestyle diseases, is crucial for the proper development of children and adolescents. State of knowledge: The contemporary approach to prevention in pediatrics is based on four levels of preventive measures. Primary prevention focuses on eliminating or reducing risk factors for diseases and shaping pro-health habits, such as a healthy diet, physical activity and vaccinations. Secondary prevention focuses on early detection of diseases in their subclinical stages, which allows for faster initiation of treatment and limiting further development of diseases. Tertiary prevention aims to prevent complications and further deterioration of health in people already affected by the disease. This includes rehabilitation, psychological support and control and treatment of chronic diseases. Quaternary prevention, which is gaining importance in recent studies, involves protecting patients from unnecessary medical interventions that may do more harm than good. Conclusion: Effective prevention in pediatrics requires an integrated approach, including cooperation between parents, teachers, medical personnel and institutions responsible for public health. Adapting activities to local conditions and actively involving children and their caregivers increase the effectiveness of prevention programs. Comprehensive, yet individualized strategies are key to improving the health of the pediatric population and preventing diseases in later stages of life.